Novel Hypolipidaemic Drugs: Mechanisms of Action and Main Metabolic Effects - Filippatos, Theodosios D.; Liontos, Angelos; Christopoulou, Eliza C.; Elisaf, Moses S. (Current Vascular Pharmacology, 2019)
Over the last 3 decades, hypolipidaemic treatment has significantly reduced both Cardiovascular (CV) risk and events, with statins being the cornerstone of this achievement. Nevertheless, residual CV risk and unmet goals in hypolipidaemic treatment make novel options necessary. Recently marketed monoclonal antibodies against proprotein convertase subtilisin/kexin type 9 (PCSK9) have shown the way towards innovation, while other ways of PCSK9 inhibition like small interfering RNA (Inclisiran) are already being tested. Other effective and well tolerated drugs affect known paths of lipid synthesis and metabolism, such as bempedoic acid blocking acetyl-coenzyme A synthesis at a different level than statins, pemafibrate selectively acting on peroxisome proliferator-activated receptor (PPAR)- alpha receptors and oligonucleotides against apolipoprotein (a). Additionally, other novel hypolipidaemic drugs are in early phase clinical trials, such as the inhibitors of apolipoprotein C-III, which is located on triglyceride (TG)-rich lipoproteins, or the inhibitors of angiopoietin-like 3 (ANGPTL3), which plays a key role in lipid metabolism, aiming to beneficial effects on TG levels and glucose metabolism. Among others, gene therapy substituting the loss of essential enzymes is already used for Lipoprotein Lipase (LPL) deficiency in autosomal chylomicronaemia and is expected to eliminate the lack of Low- Density Lipoprotein (LDL) receptors in patients with homozygous familial hypercholesterolaemia. Experimental data of High-Density Lipoprotein (HDL) mimetics infusion therapy have shown a beneficial effect on atherosclerotic plaques. Thus, many novel hypolipidaemic drugs targeting different aspects of lipid metabolism are being investigated, although they need to be assessed in large trials to prove their CV benefit and safety.
Keywords: peroxisome proliferator-activated receptor (PPAR)-alpha